Տնտեսական աճի և սոցիալ-տնտեսական տեղաշարժերի փոխառնչությունները ԼՂՀ տնտեսության զարգացման ժամանակակից պայմաններում - Ասրյան, Շ. Շ.
В статье рассмотрены последние тенденции экономического роста НКР и связанные с ними социально – экономические сдвиги. Создание условий экономического роста во всех странах, в том числе и в НКР, является главной целью экономической политики страны. Обеспечение экономического роста в любой стране создает возможности формирования новых ресурсов для решения социально – экономических задач. Изучение проблемы выявило взаимосвязь стабильного экономического роста и социально – экономических преобразований в НКР. В результате анализа экономического роста НКР сделаны предложения в необходимости структурного преобразования экономики НКР, в преодолении непропорциональности соотношения разных сфер экономики, стимулирования развития малого и среднего бизнеса и, в целом, в отношении необходимых мероприятий развития экономики НКР. In the article the latest tendencies of economic growth of NKR and related social economic shifts are examined. The creation of conditions of economic growth in all countries as well as in NKR is one of the main objectives of economic policy of the country. The provision of economic growth in any country creates opportunity of forming new resources for solving social economic problems. The study of the problem revealed interrelationship of stable economic growth and social economic transformation in NKR. As a result of analysis of economic growth of NKR suggestions are made of the necessity of structural transformation of NKR economics, the overcoming of disproportionate correlation of various spheres of economy, stimulating of small and medium business and, as a whole, with regard to taking essential measures of developing economy of NKR.
Keywords: Տնտեսագիտություն